Analysis Factors of Customer Satisfaction on Creating Consumer Loyalty at Bu Puji Sembako In Berbek Market, Berbek District, Nganjuk Regency - Eka Yuni Wulandari; Muhammad Alhada Fuadilah Habib (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The development of the business world is currently growing rapidly from time to time. This can be seen from the emergence of various business sectors. Thus business actors who have long needed a special strategy to be able to maintain their business. One of the staple food stalls that has been around for 12 years is Kios owned by Mrs. Puji at Berbek Market, Berbek District, Nganjuk Regency. The kios requires a specific strategy in order to maintain customer satisfaction and create customer loyalty. This research tries to analyze customer satisfaction factors that can create customer loyalty at Bu Puji's basic food stall. The research method used is descriptive qualitative with data sources obtained from interviews, observation, and literature study. Based on the research that has been done, the results show that Bu Puji's basic food stalls have succeeded in providing customer satisfaction so as to create consumer loyalty. The factors that cause customer satisfaction are product quality, price, service quality, emotional factors, and convenience.